Flexural behavior of circular section concrete-filled steel tubes with embedded latticed angles. (September 2022) - Hu, Liang; Song, Sha-Sha; Chen, Ju; Wang, Jun
Abstract: The flexural behavior of circular section concrete-filled steel tubes with embedded latticed angles (CFST-LA) was investigated experimentally and numerically in this paper. Eleven full-scale CFST-LA specimens were tested under four points bending load. The effects of embedded latticed angles on the flexural strengths, load-deflection curves and load-strain curves of test specimens were obtained from the test results. A finite element model (FEM) was developed and verified against test results. Based on the validated FEM, parametric studies were conducted to analyze the effect of the confinement factor, structural steel index and the relative distance of angles on the flexural strengths of the CFST-LA specimens. Both experimental and numerical results demonstrated that the flexural strengths of the CFST-LA specimens were enhanced by the embedded latticed angles. Design methods based on AISC 360–16 specifications and data points curve fitting were proposed. It is shown that both methods are able to predict the flexural strength of CFST-LA members with reasonable accuracy. Graphical abstract: Unlabelled Image Highlights: Failure mode of circular section CFSTs with embedded latticed angles subject to bending investigated. Effects of embedded latticed angles on the loading process and flexural capacity assessed. Influence of the confinement factor, structural steel index and the normalized distance of angles on the flexural strengths evaluated. Flexural design approaches for circular section CFSTs with embedded latticed angles proposed.